2015
DOI: 10.1177/0264619615575792
|View full text |Cite
|
Sign up to set email alerts
|

“A great moment . . . because of the music”: An exploratory study on music therapy and early interaction with children with visual impairment and their sighted caregivers

Abstract: The focus of this article is on how musical interaction can contribute to bonding and early interaction. This article is based on a music therapy project in a pedagogical institution for people with visual impairment. The study is qualitative and exploratory, where children with visual impairments (aged 1–4 years) and their caregivers participated in music therapy sessions over 10 weeks. Data have been collected by participant observation, video recordings, and interviews. Moments of positive interactions in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 29 publications
(37 reference statements)
1
21
0
Order By: Relevance
“…Meanwhile, the music groups provided an opportunity for individuals with AVI to console one another through hardships; these groups served as a shelter where they could feel a sense of stability that they could not feel anywhere else, and provided a place where those facing the same challenges could embrace one another for encouragement and sharing. This finding is consistent with previous studies reporting that musicing, with an aim to improve social relationships, could help individuals with AVI to form positive relationships with others, thereby reducing their sense of isolation and promoting mutual exchange (Metell, 2015). The findings also agreed with a previous study on the function of music for social groups, which reported that music, to individuals with AVI, could make a marked contribution to promoting the exchange among group members and enabling them to acquire a sense of belonging (Park et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…Meanwhile, the music groups provided an opportunity for individuals with AVI to console one another through hardships; these groups served as a shelter where they could feel a sense of stability that they could not feel anywhere else, and provided a place where those facing the same challenges could embrace one another for encouragement and sharing. This finding is consistent with previous studies reporting that musicing, with an aim to improve social relationships, could help individuals with AVI to form positive relationships with others, thereby reducing their sense of isolation and promoting mutual exchange (Metell, 2015). The findings also agreed with a previous study on the function of music for social groups, which reported that music, to individuals with AVI, could make a marked contribution to promoting the exchange among group members and enabling them to acquire a sense of belonging (Park et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…There is a high risk that parents respond to the child's apparent lack of reaction by decreasing their own interactive behaviour, which will be have a negative effect on the baby's social development (Lang, Hintermair & Sarimski, 2017). However, Metell (2015) points out that interaction and bonding are totally possible if parents use touch and their voices to establish a relationship and attend to body movements and sounds instead of the child's face (Bigelow, 1992, as cited in Metell, 2015. Bishop (1991) points out that, as the child develops, a great number of social gestures may not be learnt because the child lacks vision and does not imitate them spontaneously.…”
Section: Social Skills In Infancymentioning
confidence: 99%
“…EL VISTA is training teachers of visually impaired students and O&M specialists in the five foundational concepts of early intervention as identified by Pletcher and Younggren (2013): family-centered and relationship-based practices, natural environments, child learning, adult learning, and quality team practices. The combination of these five foundational concepts with guidance from researchers in the field of visual impairment suggests that adaptations to the child's environment that meet the child's visual needs are crucial to the child's growth and development in the areas of motor, cognition, communication, and social interactions (Alfaro, 2015;Chen et al, 2007;Dunnett, 1999;Erickson, Hatton, Roy, Fox, & Renne, 2007;Fazzi et al, 2002;Herrera, 2015;Ihsen, Troester, & Brambring, 2010;Metell, 2015). The unique curricular design employed in the EL VISTA project that forges recommended practices and personnel preparation curricular standards from both the early intervention field and the visual impairment field is leading the way in the creation of a new profession: the early intervention and visual impairment profession.…”
Section: Goalmentioning
confidence: 99%